PERAN PENTING COMPUTATIONAL THINKING TERHADAP MASA DEPAN BANGSA INDONESIA - Annisa Mauliani (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
In this study the adding of 3 theories from 10 article about Computational Thinking, Critical Thinking, and PISA Test . The aspect of Computational Thinking have correlation with Critical Thinking, and PISA Test. Critical Thinking is the basic theory to have Computational Thinking. Computational Thinking is about Dekomposisi, Abstraksi, Pattern Recognition, Algorithm. Otherwise consept of Computational Thinking is Logic and logical thinking, Algorithms and algorithmic thinking, Patterns and pattern recognition, Abstraction and generalization, Evaluation, and Automation. The questions in the PISA test do use HOTS-based type of questions. In working on HOTS-based type of questions, computational thinking and critical thinking skills are needed, therefore why Computational Thinking has an important role for the progress of the Indonesian nation. Keywords: Computational Thinking, Critical Thinking, PISA Test